Agricultural productivity growth in the European union and transition countries - Supawat Rungsuriyawiboon (2018)
The Central and Eastern Europe Countries (CEECs) have experienced significantchanges in politics, economy, and society over the past decade. Economic reform in theCEECs helped transform the structure and volume of agricultural production and resultedin significant productivity improvement. However, large differences persist among thetransition countries in the magnitude and direction of these changes. This study measuresand compares the levels and trends in agricultural productivity in transition countries withthose of the European Union (EU) countries using a panel data set on 46 Europeancountries during 1992-2002. This study employs a parametric distance function approachto measure the Malmquist total factor productivity index as well as the magnitude anddirection of technical change. Our major findings indicate that the transitioncountries achieved a higher agricultural performance and showed more input- and outputbiasedtechnical change than the EU countries. © 2007 Nova Science Publishers, Inc. All rights reserved.